Suppressing Co‐Crystallization of Halogenated Non‐Fullerene Acceptors for Thermally Stable Ternary Solar Cells. (13th October 2020) - Hultmark, Sandra; Paleti, Sri Harish Kumar; Harillo, Albert; Marina, Sara; Nugroho, Ferry Anggoro Ardy; Liu, Yanfeng; Ericsson, Leif K. E.; Li, Ruipeng; Martín, Jaime; Bergqvist, Jonas; Langhammer, Christoph; Zhang, Fengling; et al.
Abstract: While photovoltaic blends based on non‐fullerene acceptors are touted for their thermal stability, this type of acceptor tends to crystallize, which can result in a gradual decrease in photovoltaic performance and affects the reproducibility of the devices. Two halogenated indacenodithienothiophene‐based acceptors that readily co‐crystallize upon mixing are studied, which indicates that the use of an acceptor mixture alone does not guarantee the formation of a disordered mixture. The addition of the donor polymer to the acceptor mixture readily suppresses the crystallization, which results in a fine‐grained ternary blend with nanometer‐sized domains that do not coarsen due to a high T g ≈ 200 °C. As a result, annealing at temperatures of up to 170 °C does not markedly affect the photovoltaic performance of ternary devices, in contrast to binary devices that suffer from acceptor crystallization in the active layer. The results indicate that the ternary approach enables the use of high‐temperature processing protocols, which are needed for upscaling and high‐throughput fabrication of organic solar cells. Further, ternary devices display a stable photovoltaic performance at 130 °C for at least 205 h, which indicates that the use of acceptor mixtures allows to fabricate devices with excellent thermal stability. Abstract : The two non‐fullerene acceptors 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2', 3'‐d']‐s‐indaceno[1, 2‐b:5, 6‐b']dithiophene (ITIC)‐4F and ITIC‐4Cl co‐crystallize, a process that is suppressed when blended with the donor polymer PTB7‐Th. As a result, the corresponding ternary devices display stable photovoltaic performance up to 170 °C, in contrast to the binary devices that suffer acceptor crystallization. This indicates that acceptor mixtures allow to fabricate devices with excellent thermal stability.